2016
DOI: 10.1111/ecog.01961
|View full text |Cite
|
Sign up to set email alerts
|

NicheA: creating virtual species and ecological niches in multivariate environmental scenarios

Abstract: Robust methods by which to generate virtual species are needed urgently in the emerging field of distributional ecology to evaluate performance of techniques for modeling ecological niches and species distributions and to generate new questions in biogeography. Virtual species provide the opportunity to test hypotheses and methods based on known and unbiased distributions. We present Niche Analyst (NicheA), a toolkit developed to generate virtual species following the Hutchinsonian approach of an n‐multidimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
165
1
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 177 publications
(177 citation statements)
references
References 66 publications
1
165
1
10
Order By: Relevance
“…3.0 (Qiao et al 2016), with eight distinct niche centers and two radii (1.5 and 2.0, corresponding to narrow and wide niches, respectively; Supplementary material Appendix 1 Fig. 3.0 (Qiao et al 2016), with eight distinct niche centers and two radii (1.5 and 2.0, corresponding to narrow and wide niches, respectively; Supplementary material Appendix 1 Fig.…”
Section: Virtual Species In a Real Landscapementioning
confidence: 99%
“…3.0 (Qiao et al 2016), with eight distinct niche centers and two radii (1.5 and 2.0, corresponding to narrow and wide niches, respectively; Supplementary material Appendix 1 Fig. 3.0 (Qiao et al 2016), with eight distinct niche centers and two radii (1.5 and 2.0, corresponding to narrow and wide niches, respectively; Supplementary material Appendix 1 Fig.…”
Section: Virtual Species In a Real Landscapementioning
confidence: 99%
“…To facilitate this process, the workflow of the analyses developed here is included as Supplementary Material S6 to be executed in NicheA (21) and includes data to replicate this workflow (Supplementary Material S6). Step-by-step instructions to estimate N F of any species can also be found in the website of NicheA 2 …”
Section: Discussionmentioning
confidence: 99%
“…First, we highlight the importance of data curation and show a method for outlier removal in environmental dimensions based on a priori assumptions. Also, the ecological niche modeling algorithms proposed require low parameterization as they are based on the position (MVE) and density (Marble) of occurrences in an environmental space (22, 30), but also require a series of biological assumptions to make the outputs interpretable [e.g., Fundamental Niches of an ellipsoidal shape (21)]. We found that exploring algorithms of different analytical nature such as those aiming to fit environmental clusters, climatic envelopes, and logistic regressions (e.g., Marble, MVE, and Maxent) provided different scenarios of the potential distribution of Heterosporosis.…”
Section: Discussionmentioning
confidence: 99%
“…Para a visualização da distribuição das espécies em condições climáticas atuais, realizou-se uma análise de componentes principais (PCA) para reduzir a dimensionalidade e colinearidade das variáveis ambientais e utilizou-se poliedros convexos em torno de ocorrências disponíveis para cada espécie de carrapato em um espaço ambiental definido pelos três primeiros componentes gerados a partir da PCA, pois estes continham 92,43% da informação para A. cajennense ss e 88,73% da informação para A. sculptum das sete variáveis bioclimáticas originais (Material Suplementar S1); Ambos os procedimentos foram realizados usando software NicheA versão 3.0 (Qiao et al, 2016). Estes cenários são baseados na via de concentração representativa de 8,5 (RCP 8.5) e exploram o uso demográfico, socioeconômico e da terra para estimar diferentes emissões de gases .…”
Section: Obtenção Dos Dadosunclassified